Poly-epigenetic scores for cardiometabolic risk factors interact with demographic factors and health behaviors in older US Adults - Lisha Lin; Wei Zhao; Zheng Li; Scott M. Ratliff; Yi Zhe Wang; Colter Mitchell; Jessica D. Faul; Sharon L. R. Kardia; Kira S. Birditt; Jennifer A. Smith (Epigenetics)
Poly-epigenetic scores (PEGS) are surrogate measures that help capture individual-level risk. Understanding how the associations between PEGS and cardiometabolic risk factors vary by demographics and health behaviors is crucial for lowering the burden of cardiometabolic diseases. We used results from established epigenome-wide association studies to construct trait-specific PEGS from whole blood DNA methylation for systolic and diastolic blood pressure (SBP, DBP), body mass index (BMI), C-reactive protein (CRP), high- and low-density lipoprotein cholesterol (HDL-C, LDL-C), triglycerides (TG), and fasting glucose. Overall and race-stratified associations between PEGS and corresponding traits were examined in adults >50 years from the Health and Retirement Study (n = 3,996, mean age = 79.5 years). We investigated how demographics (age, sex, educational attainment) and health behaviors (smoking, alcohol consumption, physical activity) modified these associations. All PEGS were positively associated with their corresponding cardiometabolic traits (p < 0.05), and most associations persisted across all racial/ethnic groups. Associations for BMI, HDL-C, and TG were stronger in younger participants, and BMI and HDL-C associations were stronger in females. The CRP association was stronger among those with a high school degree. Finally, the HDL-C association was stronger among current smokers. These findings support PEGS as robust surrogate measures and suggest the associations may differ among subgroups.